Pemodelan SEM Partial Least Square Pada Minat Pelanggan UMKM Menggunakan QRIS sebagai Alat Pembayaran - Rahman, Yulinar; Yahya, Lailany; Isa, Dewi Rahmawaty (Research in the Mathematical and Natural Sciences, 2024)
Structural Equation Modeling (SEM) is a multivariate statistical method. in addition, SEM is a method that is able to disclose the simultaneous correlation between indicator variables (which are directly observed) and latent variables (which are not directly observed). Information and communication technology developments facilitate the growth of the digital economy. One form of implementing technology and information in the growth of the digital economy is conducting non-cash transaction. Furthermore, digital financial service are financial service that use digital technology through third paties, namely without intermediaries from banks and the general public. Technological development change business activities in financial service, especially in the digital world. The use of a QR (Quick Response) code payment system is a system that is currently popular. On January 1, 2020, Bank Indonesia officially released a standart for using the Indonesian QR code called Quick Response Code Indonesian Standard (QRIS). Thus, this research aimed to determine the factors affecting MSME customers’ interest in using QRIS as a payment method. This research employed 97 respondents’ responses obtained from distributing questionnaires to MSME (Micro, Small, and medium Enterprises) in Gorontalo City, in which the respondents were the customer who often used QRIS as the payment method. The finding indicated that public understanding and convenience affected customers’ interest in using QRIS as a payment mtehod. In comparison, the benefits and obstacles did not significantly affect customers’ interest in using QRIS as a payment method.